Community structure and spatial distribution of benthic fauna in the Bellingshausen Sea (West Antarctica) - Saiz Salinas, Jose Ignacio; García García, Francisco José; Manjón-Cabeza Clouté, María Eugenia; Parapar, Julio; Peña-Cantero, Álvaro; Saucède, Thomas; Troncoso, Jesús S.; Ramos, Ana (Polar Biology, 2008)
The structure and spatial distribution of the macrofauna community of the Bellingshausen Sea in the western sector of Antarctica was studied during the ‘BENTART–06’ oceanographic expedition. This is one of the least explored Antarctic seas. A total of 20 box cores were sampled at 11 stations ranging from 157 to 3,304 m depth, using an USNEL-type box corer (BC) dredge. Representatives of 25 higher taxa of invertebrates were collected. Deeper sampling sites were less rich in taxa (4–7 taxa), whereas the figures were higher at shallower sites (up to 17 taxa). Faunal density on the sea bottom revealed a horizontal spatial gradient from the western sites with extremely low figures (90 indiv./m2) towards the eastern ones with the highest figures (1,360 indiv./m2) close to the Antarctic Peninsula. Several abiotic factors (depth, redox, organic matter, carbonates and particle size of surficial sediments) were measured simultaneously on the sea floor to characterise the substrate preferences of the fauna. Positive correlations were found between the faunal distribution and a combination of depth, redox values, and organic matter content of sediments. This indicates decreasing availability of food in the deeper bottoms of the Bellingshausen Sea with a prevalence of depauperated bottoms dominated almost exclusively by a foraminiferans community. Ministerio de Ciencia y Tecnología; GLC2004-01856/ANT